Pelatihan Pembuatan Media Pembelajaran Berbasis IT Menggunakan Software Camtasia untuk Guru Alumni Prodi PGMI Fakultas Tarbiyah - Aflahah Aflahah; Mohammad Hefni; Ahmad Fawaid (IAIN Madura, 2020)
In the world of education, teachers are required to design IT-based learning media that are innovative, creative, efficient, and effective to increase the understanding and activeness of students in the learning process. This study describes the importance of training to make IT-based learning media by using Camtasia for the teachers who graduated from the Madrasah Ibtidaiyah Teacher Education program of Tarbiyah Faculty, Institut Agama Islam Negeri Madura. The discussion presented in this paper arises from a descriptive qualitative study since it describes the result of training to make IT-based learning media by using Camtasia software. By training the 30 teachers as participants, the result of the discussion highlights the potential of using Camtasia software media in the teaching and learning process. It can arouse the desire, interest, and motivation of students. In addition to producing student motivation and interest, IT-based learning media can also help students improve their understanding of the teacher's material(Dalam dunia pendidikan, guru dituntut mampu merancang media pembelajaran berbasis IT yang inovatif, kreatif, efisien dan efektif sehingga dapat meningkatkan pemahaman dan keaktifan peserta didik dalam proses belajar. Penelitian ini menjelaskan pentingnya pelatihan pembuatan media pembelajaran berbasis IT menggunakan Software Camtasia untuk guru alumni program studi Pendidikan Madrasah Ibtidaiyah Indonesia (PGMI), Fakultas Tarbiyah, Institut Agama Islam Negeri Madura. Diskusi penelitian ini bermula dari penelitian deskriptif kualitatif dimana penelitian ini mendeskripsikan hasil pelatihan pembuatan media pembelajaran berbasis IT menggunakan Software Camtasia. Dengan diselenggarakannya pelatihan pada 30 guru sebagai partisipan, hasil diskusi menunjukkan potensi penggunaan Software Camtasia dalam proses belajar mengajar. Dengan pemakaian media Software Camtasia dapat membangkitkan keinginan, minat serta motivasi siswa. Selain membangkitkan motivasi dan minat siswa media pembelajaran berbasis IT juga dapat membantu siswa meningkatkan pemahaman terhadap materi yang disampaikan oleh guru)